PERCEPTION STUDENT OF DEPARTMENT GUIDANCE AND COUNSELING AT UNIVERSITAS MUHAMMADIYAH METRO INTO SCHOOL COUNSELOR PROFESSION - SARI, SERLI NOVITA; ATIEKA, NURUL (Universitas Muhammadiyah Metro, 2015)
Abstract: Guidance and Counseling Teaching profession is a profession with dignity and requiring scientific competence and qualifications. Many emerging negative perception, even from students of guidance and counseling to the profession of guidance and counseling. The problem in this research is formulated as follows: